2006
DOI: 10.1021/ef060189l
|View full text |Cite
|
Sign up to set email alerts
|

Oil Reservoir Characterization via Crude Oil Analysis by Downhole Fluid Analysis in Oil Wells with Visible−Near-Infrared Spectroscopy and by Laboratory Analysis with Electrospray Ionization Fourier Transform Ion Cyclotron Resonance Mass Spectrometry

Abstract: In the first study of its kind, we analyze heavy ends of crude oils to characterize oil reservoirs by both in situ downhole fluid analysis (DFA) in oil wells along with heavy-end fingerprinting utilizing ultrahigh resolution mass spectrometry. One of the biggest problems in the exploitation of oil reservoirs in high-cost settings is the difficulty of characterizing flow connectivity or compartmentalization of the various permeable zones. Standard industry methods to determine compartmentalization either fail o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 70 publications
3
52
0
Order By: Relevance
“…Hence, ESI FT-ICR MS and GC×GC can be combined to provide a detailed description of the composition of almost an entire crude oil. The ESI FT-ICR MS method has been described previously, and details particular to this application are presented as Supplementary Material (Betancourt et al, 2009;Mullins et al, 2006;Senko et al, 1996).…”
Section: Esi Ft-icr Msmentioning
confidence: 99%
“…Hence, ESI FT-ICR MS and GC×GC can be combined to provide a detailed description of the composition of almost an entire crude oil. The ESI FT-ICR MS method has been described previously, and details particular to this application are presented as Supplementary Material (Betancourt et al, 2009;Mullins et al, 2006;Senko et al, 1996).…”
Section: Esi Ft-icr Msmentioning
confidence: 99%
“…A recent study has shown that the asphaltene chemistry is very similar in an hydraulically unconnected stacked-sand sequence. [17] A similar investigation is being done here; we anticipate that there will be no large chemical differences between asphaltenes found at different depth to account for the color differences. Asphaltene concentration is the key issue.…”
Section: The Reservoirmentioning
confidence: 52%
“…8, DFA color inversions (higher color fluid higher in the oil column), thus asphaltene concentration inversions are observed. [26] For example, crude oil A has three times the color magnitude of crude oil B, thus three times the asphaltene content. [27] Thus a sealing barrier is between these zones.…”
Section: Gor (Scf/bbl)mentioning
confidence: 99%